Association between liver fibrosis and incident dementia in the UK Biobank study. (20th June 2022) - Parikh, Neal S.; Kamel, Hooman; Zhang, Cenai; Kumar, Sonal; Rosenblatt, Russell; Spincemaille, Pascal; Gupta, Ajay; Cohen, David E.; de Leon, Mony J.; Gottesman, Rebecca F.; Iadecola, Costantino
Abstract: Background and purpose: There is growing recognition that chronic liver conditions influence brain health. The impact of liver fibrosis on dementia risk was unclear. We evaluated the association between liver fibrosis and incident dementia in a cohort study. Methods: We performed a cohort analysis using data from the UK Biobank study, which prospectively enrolled adults starting in 2007, and continues to follow them. People with a Fibrosis‐4 (FIB‐4) liver fibrosis score >2.67 were categorized as at high risk of advanced fibrosis. The primary outcome was incident dementia, ascertained using a validated approach. We excluded participants with prevalent dementia at baseline. We used Cox proportional hazards models to evaluate the association between liver fibrosis and dementia while adjusting for potential confounders. Results: Among 455, 226 participants included in this analysis, the mean age was 56.5 years and 54% were women. Approximately 2.17% (95% confidence interval [CI] 2.13%–2.22%) had liver fibrosis. The rate of dementia per 1000 person‐years was 1.76 (95% CI 1.50–2.07) in participants with liver fibrosis and 0.52 (95% CI 0.50–0.54) in those without. After adjusting for demographics, socioeconomic deprivation, educational attainment, metabolic syndrome, hypertension, diabetes, dyslipidemia, and tobacco and alcohol use, liver fibrosis was associated with an increased risk of dementia (hazard ratio 1.52, 95% CI 1.22–1.90). Results were robust to sensitivity analyses. Effect modification by sex, metabolic syndrome, and apolipoprotein E4 carrier status was not observed. Conclusion: Liver fibrosis in middle age was associated with an increased risk of incident dementia, independent of shared risk factors. Liver fibrosis may be an underrecognized risk factor for dementia. Abstract : In a retrospective cohort analysis of approximately 450, 000 participants in the UK Biobank study, individuals with high probability of advanced liver fibrosis had a 1.5‐fold higher risk of incident dementia. Results were consistent after accounting for potential confounders and were robust to multiple sensitivity analyses and approaches. These findings suggest that liver fibrosis may detrimentally impact future cognitive health.